Penyuluhan Mengenai Peran Penting BUMDes dalam Menggerakkan Ekonomi Masyarakat - Dewi Mahmuda; Wa Ode Al Zairani; Kartina Yati; Lutkifli Lutkifli (Community Engagement and Emergence Journal (CEEJ), 2020)
The condition of people in Lawela Village, who are mostly low-income and uncertain, makes this village need BUMDes as a village business institution that accommodates business creativity with the community. The purpose of this PkM is to provide counseling on the importance of the existence of Village-Owned Enterprises (BUMDes) to drive the economy in the Village and maximize the ability of financial managers regarding accountability and transparency in future BUMDes financial reporting. The method used is counseling and mentoring. The result was an increase in people's understanding of the establishment and management of BUMDes. This activity also succeeded in educating the public about SAK-ETAP as signs of BUMDes financial reporting. This PkM has been able to fully explain to the people of Lawela Village about BUMDes, both in terms of institutional and management of BUMDes financial administration. The community has acquired knowledge on how to optimize the potential of Lawela Village commercially that is very useful to support local community income. Key words: BUMDes, village finance